Identification of mitophagy-related biomarkers and immune infiltration in polycystic ovarian syndrome by bioinformatic study - Hongjuan Ye; Xicheng Wang; Zhiying He (Heliyon)
Background: Polycystic ovarian syndrome (PCOS) is a common endocrine and metabolic disorder in women of reproductive age. In this study, we aimed to investigate the potential prognostic value of mitophagy-related genes in PCOS patients and to analyze their role in immune infiltration during PCOS pathogenesis and progression. Methods: Training datasets were used for differential expression genes. Gene ontology annotations and Kyoto encyclopedia of genes and genomes signaling pathway enrichment analysis were performed. The potential biomarkers of mitophagy-related and immune infiltration in PCOS were screened by protein-protein interaction network using different algorithms, and the area under the curve was calculated to analyze their diagnostic value. The test datasets were used to validate the expression of hub genes, and receiver operating characteristic curves were used to evaluate the predictive effect of hub genes. Results: Five hub genes: CTSD, IGF2R, ATP13A2, NAPA and GRN were identified as the potential diagnostic biomarkers of immune-mitophagy-related PCOS through five algorithms. GRN and NAPA were validated to be significantly different in oocytes and granulosa cells between primary and secondary follicles, respectively. Based on the single sample Gene Set Enrichment Analysis score, the infiltration of 4 immune cell types in PCOS was associated with PCOS and mitophagy. Specifically, the hub gene GRN showed a positive correlation with monocytes and plasmacytoid dendritic cells, while hub gene NAPA was negatively correlated with gamma delta T cell. Conclusions: The current study identified immune-mitophagy-related hub genes for prognostic biomarkers of PCOS, which provided an innovative insight for the prevention and treatment of PCOS.